A retrospective study investigating the rate of HER2 discordance between primary breast carcinoma and locoregional or metastatic disease - Chan, Arlene; Morey, A.; Brown, B.; Hastrich, D.; Willsher, P.; Ingram, D. (2012)
Background: Overall survival of HER2 positive metastatic breast cancer patients has been significantly improved with inclusion of trastuzumab to chemotherapy. Several studies have demonstrated discordant HER2 status in the primary and metastatic tumour. However, rates of discordance vary considerably in published reports. Methods: Information collected prospectively was analysed for all patients seen from 1999 to 2009 with primary breast cancer and who had biopsy of a local or distant recurrence. Patients were included if adequate tissue was available from both paired samples. Recurrent samples included fine needle aspirations, core and excisional biopsies. HER2 status in all paired samples was assessed by in-situ hybridisation by a single pathologist in a national reference laboratory. This was compared with HER2 immunohistochemistry results provided in the course of routine diagnosis at regional laboratories. Results: In total, 157 patients with recurrent (n = 137; 87.3%) or synchronous primary and metastatic (n = 20; 12.7%) breast cancer had biopsy of the metastatic site. The study population comprised of 116 patients with adequate tissue in both primary and metastasis. The concordance between HER2 status of the paired samples by local immunohistochemistry testing and central in-situ hybridization were 78% and 99%, respectively. Only one patient demonstrated HER2 discordance - primary lesion was positive whilst a metastatic site was negative.Conclusions: This single institution study demonstrated a low rate of HER2 discordance between primary and recurrent breast cancer as assessed by in-situ hybridisation. This contrasts to results reported by others, which may be explained by differences in study methodology, definition of recurrent disease samples and generally small numbers of patients assessed. Despite the current findings, the decision to obtain metastatic tissue for evaluation is influenced by other factors. These include disease-free interval, which may raise the possibility of a new malignancy and the accuracy of initial HER2 assessment of the primary tumour.